Developing the first-ever global learning strategy to frame the future of learning for achieving public health goals - Gaya Gamhewage; Christos Mylonas; Mohamed Mahmoud; Oliver Stucke (Journal of Oral Biology and Craniofacial Research)
Health is at the forefront of everyone's mind. Every country on the planet is currently experiencing the COVID19 pandemic, which is not just causing death and disease, but damaging societies and economies on a significant scale across the world.1 The current pandemic has brought into sharp focus the socio-economic factors and inequities in how people experience health and ill health and shone a spotlight on the need for lifelong learning so that health professionals, volunteers, and the public alike can adapt and respond to health threats.But even before the pandemic, the world was changing profoundly in the past few decades, and these changes impacted people's health. Unfortunately, the role of education and learning in the health domain has not kept pace with these changes. Many factors converge to create a major evolution, and some say, revolution, in how education, training and learning for health can and should be leveraged to protect and promote people's health. This paper summarizes some of the critical ideas of an 18-month process to create the first-ever global learning strategy for health by the World Health Organization.